2018
DOI: 10.3389/fcimb.2018.00355
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Hepatitis B Virus Precore/Core Mutations and the Progression of Severe Liver Disease

Abstract: Viral mutations acquired during the course of chronic hepatitis B virus (HBV) infection are known to be associated with the progression and severity of HBV-related liver disease. This study of HBV-infected Saudi Arabian patients aimed to identify amino acid substitutions within the precore/core (preC/C) region of HBV, and investigate their impact on disease progression toward hepatocellular carcinoma (HCC). Patients were categorized according to the severity of their disease, and were divided into the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…A number of studies have focused on detecting aa changes possibly related to different clinical stages. The mutations T1753C and A1762T/G1764A (K130M/V131I in HBx) of basal core promoter, for example, were identified as possible prognostic markers for HCC [38,39] , while HBc aa mutations F24Y, E64D, E77Q, A80I/T/V, L116I, and E180A were linked to the development of cirrhosis and HCC [40] . In our study, one of the aa changes detected, P79Q, was exclusively observed in the HCC group.…”
Section: Strategymentioning
confidence: 99%
“…A number of studies have focused on detecting aa changes possibly related to different clinical stages. The mutations T1753C and A1762T/G1764A (K130M/V131I in HBx) of basal core promoter, for example, were identified as possible prognostic markers for HCC [38,39] , while HBc aa mutations F24Y, E64D, E77Q, A80I/T/V, L116I, and E180A were linked to the development of cirrhosis and HCC [40] . In our study, one of the aa changes detected, P79Q, was exclusively observed in the HCC group.…”
Section: Strategymentioning
confidence: 99%
“…16 Hepatitis B virus precure and core region mutations might be associated with HCC tumorigenesis. 17 In this study, when patients received a diagnosis, the BCLC stage was associated with antiviral treatment and baseline HBV DNA level.…”
Section: Discussionmentioning
confidence: 82%
“…Most pre-C/C mutations are generated during HBeAg seroconversion. Several types of HBV pre-C/C mutations, such as G1896A, A1762T, and G1764A, were reportedly related to disease severity [9,19,29]. Also, the HBeAg positive rate was signi cantly lower in the HCC group than the CHB group.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of mutations to the HBV genome have been reported, resulting amino acid substitutions during long-term infection, some of which could serve as markers to predict the development of HBV-associated HCC [6,7], such as mutations in the pre-surface antigen (pre-S) (i.e., deletion to the preS1 [W4P/R] and pre-S2 start codon deletion, pre-core (i.e., nucleotide 1896(G1896A), or a double mutation to the basal core promoter (BCP) and X regions (V5M) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%